Pelatihan Teknik Dasar Sepakbola pada Mahasiswa PJKR SD FIKK UNM - Akbar Sudirman; Hasbunallah Hasbunallah; Ramli Ramli; Muhammad Harliawan (Universitas Negeri Surabaya, 2023)
Knowledge and mastery of the basic techniques of playing soccer have not been entirely mastered by PJKR SD students who have programmed football courses. Some of them did not graduate so they cannot program advanced soccer courses. This is because the background or branch of each student varies and the frequency of face-to-face meetings in lectures is considered insufficient to master all the basic techniques in football, so students need additional time outside class hours such as practicing or repeating lecture material to adjust to their skills. Therefore, this training can at least provide a clear picture of the basic techniques of playing soccer and improve their skills in mastering the basic techniques of football. The methods used in this service are demonstration and lecture methods so that through this training students can skillfully demonstrate basic football techniques ranging from simple basic techniques to more complex techniques. Keywords: exercise; basic technique; football; student